Moving bodies to moving minds: a study of the use of motion-based games in special education - Kosma, Panagiotis; Ioannou, Andri; Retalis, Symeon (My University, 2018)
From an embodied learning perspective, the active human body can alter the function of the brain and therefore, the cognitive process. In this work, children’s activity using motion-based technology is framed as an example of embodied learning. The present investigation focuses on the use of a series of Kinect-based educational games by 31 elementary students with special educational needs in mainstream schools, during a five-month intervention study. Results based on psychometric pre-post testing in conjunction with games-usage analytics, a student attitudinal scale, teachers’ reflection notes and teacher interviews, demonstrated the positive impact of the games on children’s short-term memory skills and emotional stage. Overall, the study improves our understanding of embodied learning via motion-based technology in teaching and learning with children with special educational needs.
Keywords: Educational games; Embodied cognition; Embodied learning; Inclusive education; Kinect-based games; Kinesthetic learning; Motion-based technology; Students with special educational needs